Why nursing? Applying a socio‐ecological framework to study career choices of double degree nursing students and graduates. (12th October 2012) - Hickey, Noelene; Sumsion, Jennifer; Harrison, Linda
Abstract Aim To report a study that investigated the career development, aspirations, and choices of undergraduate students and graduates of nursing double degree programmes. Background Over one‐third of Australian undergraduate nursing students study by double degree mode. Their career destinations will have an impact on the availability of graduates in a time of nursing shortages, but little is known about why nursing students choose double degrees or take up a career in nursing vs. the other specialization. Design A qualitative study using two longitudinal methods. Methods The study was conducted in 2008–2009 with 68 participants from an Australian regional university offering double degrees in nursing. A time series method involved interviews with 12 first year students followed by focus group interviews with 22 final year students. A longitudinal method involved repeated interviews with 34 graduates. Interview transcripts were analysed thematically. Results Enrolment in a double degree was influenced by advice from significant others; previous experiences of health care; and the anticipated rewards associated with a choice of two careers. Career development and decisions of undergraduates were influenced by intrinsic and extrinsic rewards distinctive to each area of specialization and marketing and job availability. For graduates, the impact of workplace experiences such as prior practicums and past and present workplace support were foremost. Conclusion This study provides previously unknown information about double degree nursing students' and graduates' career development and career choices over time. A socio‐ecological framework adapted to nursing enabled a broad understanding of the many environments and contexts that confirm or discourage a nursing career.